The effect of vitamin D on primary dysmenorrhea with vitamin D deficiency: a randomized double-blind controlled clinical trial. (2nd June 2016) - Moini, Ashraf; Ebrahimi, Tabandeh; Shirzad, Nooshin; Hosseini, Reihaneh; Radfar, Mania; Bandarian, Fatemeh; Jafari-Adli, Shahrzad; Qorbani, Mostafa; Hemmatabadi, Mahboobeh
Abstract: Dysmenorrhea is common among women of reproductive age. This study aim was to investigate the effect of vitamin D (vit D) supplementation in treatment of primary dysmenorrhea with vit D deficiency. A randomized double-blind placebo-controlled clinical trial was conducted on 60 women with primary dysmenorrhea and vit D deficiency referred to our clinic at Arash Women's Hospital from September 2013 to December 2014. Eligible women were randomly assigned into treatment and control groups (30 in each group). Individuals in the treatment group received 50 000 IU oral vit D and the control group received placebo weekly for eight weeks. After two months of treatment, there was a significant difference in serum vit D concentration between the two groups ( p  <   0.001). Pain severity decreased significantly in treatment group after eight weeks of treatment. There was a significant difference in pain intensity between the two groups after eight weeks of treatment and one month after the end of treatment ( p  <   0.001 for both). A weekly high dose (50 000 IU) oral vit D supplementation for eight weeks in patients with primary dysmenorrhea and vit D deficiency could improve pain intensity.